EARLY SCHOOL LEAVING RISKS RELATED TO EDUCATIONAL INSTITUTION - Kaniņa, Inguna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
Some of the main challenges in contemporary education systems are decrease of students learning motivation, students, who don’t engage in academic work and early school leaving. In Latvia the percentage of early school leavers still remains high. Main factors reported as the reason for early school leaving were not only risks related to students personality traits, family or social environment, but also risks related to school environment, diverging comprehension of the problems related to at-risk youth among teachers and school staff and different approaches within each school to prevent early school leaving. The method used in the research was questionnaires (with closed and open questions). 195 teachers from comprehensive schools (all districts) in Latvia were involved. The main goal of the research is to analyze  teachers comprehension and assessment on early school leaving risks related to school environment and to analyze teachers views about possibilities to identify at-risk youth at an early stage. Another goal of the research is to create a sustainable action plan, to reduce early school leaving risks related to school environment